Development of a consensus-based delineation guideline for locally recurrent rectal cancer. (December 2022) - Piqeur, Floor; Hupkens, Britt J.P.; Nordkamp, Stefi; Witte, Marnix G.; Meijnen, Philip; Ceha, Heleen M.; Berbee, Maaike; Dieters, Margriet; Heyman, Sofia; Valdman, Alexander; Nilsson, Martin P.; Nederend, Joost; et al.
Highlights: Delineation in LRRC is complex due to heterogeneous disease and absence of guidelines. Inter-observer variation in LRRC is large. Multidisciplinary target volume definition is essential. QA data from PelvEx II trial will provide further insight in target volumes. Abstract: Background and purpose: Neoadjuvant chemoradiotherapy (nCRT) is used in locally recurrent rectal cancer (LRRC) to increase chances of a radical surgical resection. Delineation in LRRC is hampered by complex disease presentation and limited clinical exposure. Within the PelvEx II trial, evaluating the benefit of chemotherapy preceding nCRT for LRRC, a delineation guideline was developed by an expert LRRC team. Materials and methods: Eight radiation oncologists, from Dutch and Swedish expert centres, participated in two meetings, delineating GTV and CTV in six cases. Regions at-risk for re-recurrence or irradical resection were identified by eleven expert surgeons and one expert radiologist. Target volumes were evaluated multidisciplinary. Inter-observer variation was analysed. Results: Inter-observer variation in delineation of LRRC appeared large. Multidisciplinary evaluation per case is beneficial in determining target volumes. The following consensus regarding target volumes was reached. GTV should encompass all tumour, including extension into OAR if applicable. If the tumour is in fibrosis, GTV should encompass the entire fibrotic area. Only if tumour can clearly be distinguished from fibrosis, GTV may be reduced, as long as the entire fibrotic area is covered by the CTV. CTV is GTV with a 1 cm margin and should encompass all at-risk regions for irradical resection or re-recurrence. CTV should not be adjusted towards other organs. Multifocal recurrences should be encompassed in one CTV. Elective nodal delineation is only advised in radiotherapy-naïve patients. Conclusion: This study provides a first consensus-based delineation guideline for LRRC. Analyses of re-recurrences is needed to understand disease behaviour and to optimize delineation guidelines accordingly.